Can Results-Based Financing Improve the Effectiveness of Short-Term Education and Skills Training Programs? - World Bank (World Bank, Washington, DC, 2021)
Globally, an estimated 267 million youth aged between 15 and 24 are neither in education nor employed, with most of these youth residing in Sub-Saharan Africa and South Asia. This number is likely to increase substantially due to the Coronavirus (COVID-19) pandemic. Short-term education and skills training programs can help unemployed and out-of-school youth acquire the qualifications and skills they need to secure and maintain productive jobs. Such training programs typically combine elements of classroom education with more practical workplace training and are offered by governments, often in partnership with the private sector. Given the large amount of money that governments channel into such programs, there is a growing interest in using results-based financing (RBF) to maximize returns on their investment. This study explored whether the use of financial incentives for training providers and participants improved the impact of short-term education and skills training programs on out-of-school and unemployed youth.